2013
DOI: 10.4103/0970-1591.120107
|View full text |Cite
|
Sign up to set email alerts
|

Penile growth in response to hormone treatment in children with micropenis

Abstract: Introduction:Micropenis is defined as a stretched penile length 2.5 standard deviations less than the mean for age without the presence of any other penile anomalies, such as hypospadias. The term refers to a specific disorder that has a known set of causative factors and defined treatment modalities. The purpose of this study was to determine the effect of hormonal therapy on the gonadal response and penile growth in children who presented with micropenis.Materials and Methods:Children (<18 years) who met the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In this study, prepubertal children were treated with 25 mg of exogenous parenteral testosterone enanthate once a month for 3 months, and pubertal or postpubertal children were treated with intramuscular hCG once a week for 6 weeks. Exogenous administration of hormone replacement in these boys resulted in a significant increase in SPL and suggests that these treatments could be the primary form of therapy for micropenis in paediatric patients ( 25 ). In addition to exogenous testosterone, topical applications have been studied in the micropenis population.…”
Section: Non-surgical Managementmentioning
confidence: 99%
“…In this study, prepubertal children were treated with 25 mg of exogenous parenteral testosterone enanthate once a month for 3 months, and pubertal or postpubertal children were treated with intramuscular hCG once a week for 6 weeks. Exogenous administration of hormone replacement in these boys resulted in a significant increase in SPL and suggests that these treatments could be the primary form of therapy for micropenis in paediatric patients ( 25 ). In addition to exogenous testosterone, topical applications have been studied in the micropenis population.…”
Section: Non-surgical Managementmentioning
confidence: 99%
“…In patients with idiopathic hypogonadotropic hypogonadism and micropenis, Sun-Ouck et al and Rajendra et al found a significant increase of the testicular volume after medical treatment [ 79 , 80 ].…”
Section: Systematic Review To Address Questionmentioning
confidence: 99%
“…increase in penile length [4], the androgen-AR signaling pathway appears to be preserved even in the prepubertal period when physiological masculinization does not progress. Mutations in AR lead to androgen insensitivity syndrome (AIS), a relatively common form of 46,XY disorders of sex development (DSD) [5].…”
mentioning
confidence: 97%